Perceptions of primary health care physicians about the prescription of antibiotics in Saudi Arabia: Based on the model of Theory of planned behaviour - Faten Alradini; Asmatanzeem Bepari; Bashayer Hussain AlNasser; Ethar Fahad AlGheshem; Waad Khalid AlGhamdi (Elsevier, 2021)
Introduction: Knowledge of different factors that influence physician decision-making in general practice for prescribing antibiotics is vital for successfully implementing antimicrobial stewardship interventions. The Theory of planned behaviour (TPB) is an established model that describes how cognitions drive human behaviour. Objectives: The present study was performed to identify the socio-cultural and behavioural determinants that affect antibiotics prescription behaviour among primary care physicians and estimate the awareness about antibiotic resistance of public health importance. Methodology:: The questionnaire was divided into three sections: Section-I, which contained demographic content. Section-II contained 21 question items measuring attitudes, subjective norms, perceived behavioural control, and behavioural intentions of the prescribers. Section III had 12 questions related to knowledge about antibiotic resistance. As determined by Cronbach's α for each set of measured constructs of questionnaire scale, the internal consistency was good (α ≥ 0.7). The participants' socio-cultural and behavioural determinants were graded in 3 categories depending upon the mean score, while frequencies were used to estimate antibiotic resistance awareness. The data was analyzed by calculating the one-way ANOVA and by post-hoc Tukey-Kramer HSD multiple comparison test. Results: Four hundred thirty-four primary health care physicians responded to the questionnaire, and data was statistically investigated. Participants' knowledge of antibiotic-resistant bacteria was poor with greater behavioural intentions to prescribe antibiotics, but a positive attitude and acceptable perceived social pressure towards antibiotics. Conclusion: Our study showed that awareness towards antibiotic-resistant bacteria among primary care physicians of Saudi Arabia stands insufficient but favourable attitude and satisfactory social pressure towards antibiotics with greater behavioural intentions to prescribe antibiotics. The continued medical education (CME) and frequent training interventions can increase these parameters of rational prescribing practice for antibiotics.